Vaccination prospect against Brugian filariasis : candidate vaccines to block zoonotic transmission - Abdullah, Wan Omar; Basir, Rusliza; Abd. Majid, Roslaini (Universiti Putra Malaysia Press, 2012)
Toward the control and possible eradication of lymphatic filaraisis a new paradigm is into the development of antifilarial nucleic acid vaccine i.e to genetically engineered vaccines that can block zoonotic transmission of brugian filariasis. This vaccine may form the basis of a possible elimination of microfilariae in animal reservoirs that break zoonotic transmission from animals to humans.